2021
DOI: 10.1021/acs.est.1c02471
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to GenX and Its Novel Analogs Disrupts Hepatic Bile Acid Metabolism in Male Mice

Abstract: Due to its wide usage and recent detection in environmental matrices, hexafluoropropylene oxide dimer acid (HFPO–DA, commercial name GenX) has attracted considerable attention. Here, we explored and compared the toxicity of GenX and its novel analogs with that of perfluorooctanoic acid (PFOA) to provide guidance on the structural design and optimization of novel alternatives to poly- and perfluoroalkyl substances (PFASs). Adult male BALB/c mice were continuously exposed to PFOA, GenX, perfluoro-2-methyl-3,6-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 71 publications
2
30
0
Order By: Relevance
“…Toxicological investigations have shown that 6:2 F-53B has potential bioaccumulation and endocrine disrupting effects, causing liver damage and activating the peroxisome proliferator-activated receptor pathway in the kidney. This alternative was revealed to be even stronger biological toxicity than PFOS. HFPO-DA also exhibited hepatotoxicity comparable to PFOA, while 6:2 FTS showed clear bioaccumulation and moderate hepatotoxic effects. , The high mobility and adverse toxicological implications of short-chain potassium perfluorobutane sulfonic acid (PFBS) could result in important issues for health and the environment. , …”
Section: Introductionmentioning
confidence: 99%
“…Toxicological investigations have shown that 6:2 F-53B has potential bioaccumulation and endocrine disrupting effects, causing liver damage and activating the peroxisome proliferator-activated receptor pathway in the kidney. This alternative was revealed to be even stronger biological toxicity than PFOS. HFPO-DA also exhibited hepatotoxicity comparable to PFOA, while 6:2 FTS showed clear bioaccumulation and moderate hepatotoxic effects. , The high mobility and adverse toxicological implications of short-chain potassium perfluorobutane sulfonic acid (PFBS) could result in important issues for health and the environment. , …”
Section: Introductionmentioning
confidence: 99%
“…57 PFAS enrichment in the blood could activate the peroxisome proliferator-activated receptor (PPARα), thereby reducing Oatp expression and OATP activity. 57 Additionally, the activities of cytoplasmic proteins for binding with PFASs in hepatocytes, such as liver− fatty acid binding protein (L-FABP), 58 were disrupted at high doses of PFASs (hexafluoropropylene oxide dimer acid (HFPO-DA), 2−5 μg/g; PFOA, 3−20 μg/g), 59,60 which may explain the decreased transport efficiency from the blood to liver observed in the H group (2 μg/g PFOA).…”
Section: Partitioning Of Pfass Into Tissuesmentioning
confidence: 99%
“…[97] Disruption of hepatic bile acid metabolisms has recently been associated with exposure to a slew of organic pollutants, specifically GenX, its analogs, and PFAS. [98][99][100] The removal of these substances using bile acid sequestrants, or hypocholesterolemic agent-containing polymers, has gained popularity given their high experimental sorption efficiency. [96,[101][102][103] Some of these sequestrants include hydrogels such as Enterosgel and cellulose-based materials.…”
Section: Enterosorbents For Excess Bile Acid Removal Due To Organic C...mentioning
confidence: 99%